On the nature of structure in structural priming. (10th November 2017) - Kwon, Nayoung; Lee, Yoonhyoung
Abstract: Like Branigan & Pickering (B&P), we agree that processing evidence is important for linguistic theorization; however, without much evidence of priming of hierarchical argument structure independent of linear ordering, the nature of "structure" in structural priming remains unclear. Consequently, it is an empirical question whether structural priming and acceptability judgments tap into cognitive processes of a similar nature.